Milk Fat Globule Membrane Inhibits NLRP3 Inflammasome Activation and Enhances Intestinal Barrier Function in a Rat Model of Short Bowel. Issue 5 (24th August 2018) - Li, Ying; Wu, Jiang; Niu, Yang; Chen, Honghao; Tang, Qingya; Zhong, Yan; Lambers, Tim T.; Cai, Wei
Abstract: Background: The milk fat globule membrane (MFGM) contains various bioactive components which have been shown to maintain gut barrier integrity. This study aimed to evaluate the protective effects of MFGM on intestinal barrier function and its possible mechanisms in a rat model of short bowel syndrome (SBS). Materials and Methods: Five‐week‐old male Sprague‐Dawley rats were divided into 3 groups (n = 8 per group), consisting of Sham group and rats submitted to massive small‐bowel resection then supplemented with either water (SBS) or 1.5g/kg/d MFGM (SBS+MFGM) by daily gavage. Rats were sacrificed on day 15 postoperation. Intestinal adaptation, gut permeability, bacterial translocation (BT), expression of tight junction proteins, mucin 1 (MUC1), and nucleotide‐binding oligomerization domain leucine‐rich repeat and pyrin domain–containing protein 3 (NLRP3) pathway in the ileum were evaluated. Results: Both SBS+MFGM and SBS groups exhibited lower body weight and higher ileum villus height than Sham group, but no difference was detected between each other. SBS group had significantly higher intestinal permeability and BT rate than other groups ( P < .05). Compared with SBS rats, SBS+MFGM group showed higher expression of tight junction proteins and MUC1, lower expression of NLRP3 and caspase‐1 in the ileum, as well as lower interleukin (IL)‐1β but higher IL‐18 levels in ileum tissue. Conclusions: Supplementation of MFGM helps to modulate NLRP3 inflammasome activation and enhances gut barrier integrity in rats after massive small‐bowel resection, which provides experimental support for potential applications of MGFM in intestinal barrier dysfunction, although further studies are needed